assenger information system (PIS) for Kuantan - Tanjung Lumpur bus route - Insyirah, Mohd Yunus (2012)
The main purpose of this study is to provide information about public transportation which is public bus to people living around Tanjung Lumpur area. The dissemination of information about public transportation that is available is very important in order to inform to public bus users about the existence of public transportation thereby can increase the awareness of local residents about the benefits of using public transport. If provided public transportation is not being used and total of passengers is too little, the bus company had to stop the bus operation and this will give problems to low-income residents who still want to use public transport. Public transportation information that need to be considered are bus routes, bus travel time, and location of bus stops. This study used the concept of geographic information system in conducting inventory of existing bus facilities. In addition, the questionnaire surveys and interviews were also conducted to obtain information on bus operations along Kuantan to Tanjung Lumpur bus route. Next, information about public transportation services can be disseminated.